The Influence Mechanism of Interaction Quality in Live Streaming Shopping on Consumers’ Impulsive Purchase Intention - Li, Guangming; Jiang, Yue; Chang, Liting (Frontiers in Psychology, 2022)
As an emerging mode of online shopping, live streaming shopping has the characteristics of high interactivity. Live streaming shopping has achieved many positive results, but it leads to the phenomenon of consumers’ impulsive purchase. To analyze the reasons for impulsive purchase intention, we can make up for the lack of attention paid to this issue. Therefore, this study explores the influence mechanism of interaction quality between anchors and consumers on consumers’ emotion and impulsive purchase intention from the perspective of interaction quality combined with cognitive evaluation theory. A total 407 samples were collected by a questionnaire survey to test the research model. The results showed that: interaction quality (responsiveness, professionalism, informativeness, and personalization) had a significantly positive impact on consumers’ emotion; consumers’ emotion played a mediating role between interaction quality and impulsive purchase intention; consumers’ extroverted personality significantly negatively moderated the relationship between professionalism, informativeness and consumers’ emotion. This study can provide theoretical basis and reference for enterprises and anchors to carry out marketing activities and consumers’ rational consumption.